Mechanisms of Mitotic Kinase Regulation: A Structural Perspective - Welburn, Julie P. I.; Jeyaprakash, A. Arockia (Frontiers in Cell and Developmental Biology, 2018)
Protein kinases are major regulators of mitosis, with over 30% of the mitotic proteome phosphorylated on serines, threonines and tyrosines. The human genome encodes for 518 kinases that have a structurally conserved catalytic domain and includes about a dozen of cell division specific ones. Yet each kinase has unique structural features that allow their distinct substrate recognition and modes of regulation. These unique regulatory features determine their accurate spatio-temporal activation critical for correct progression through mitosis and are exploited for therapeutic purposes. In this review, we will discuss the principles of mitotic kinase activation and the structural determinants that underlie functional specificity.